Current Understanding of the Gut Microflora in Subjects with Nutrition-Associated Metabolic Disorder Such as Obesity and/or Diabetes: Is There Any Relevance with Oral Microflora? - Yumoto, Hiromichi; Uebanso, Takashi; Shimohata, Takaaki; Takahashi, Akira (Current oral health reports, 2019)
Purpose of Review The oral cavity is one of the main gateways to the whole body and leads to the gastrointestinal tract. Both oral cavity and gastrointestinal tract have complex ecosystems of microorganisms called microbiota. Recent studies have shown that altered local microbiome in human, such as gut microflora, is associated with various systemic diseases. This review focuses on the association between the microbiota at local sites, such as gut and oral cavity, and the systemic diseases, especially nutrition-associated metabolic disorder, such as obesity and/or diabetes. Recent Findings The gut microbiota has a potential for regulation in host immune system and metabolisms, such as energy, glucose, and lipid, and is therefore an additional contributing environmental factor to the pathophysiology of obesity and diabetes as well as gut infectious inflammatory diseases. In addition, oral microorganisms play important roles as reservoirs for exacerbation of gut diseases, and altered oral microbial profiles causing periodontal diseases, which is one of common oral infectious diseases, has been also associated with several systemic diseases including diabetes. Summary It is necessary to consider that impaired oral microbiota, called oral dysbiosis, may affect the metabolic disorders leading to obesity and diabetes in addition to the gut inflammatory diseases via alteration of gut microflora. The relevance of oral microflora to gut dysbiosis leading to nutrition-associated metabolic disorder should be addressed as future investigations.